Sosialisasi penggunaan Aplikasi Satu Data Kesehatan (ASDK) Untuk Implementasi Sistem Pencatatan Integrasi Pelayanan Kesehatan Primer (ILP) Di Kabupaten Tulungagung - Asri; Mundakir; Alfian, Afan; Aziz, M. Aminudin (Indonesian Academia Health Sciences Journal, 2024)
The socialization of the Health Single Data Application (ASDK) in Tulungagung Regency aims to enhance the integration of primary healthcare service (ILP) recording through the utilization of information technology. This activity was conducted on June 15, 2024, involving 50 healthcare workers from various community health centers. The methods used included intensive training, data recording simulations, and evaluation through pre-test and post-test assessments. The evaluation results indicated a significant improvement in participants' understanding, with 85% reporting increased proficiency in using ASDK. Additionally, the participants' enthusiasm during the training sessions demonstrated the effectiveness of interactive approaches and the use of visual media. The main challenges in implementing ASDK were the lack of human resource readiness and uneven technological infrastructure. Therefore, recommendations included regular training and the development of more user-friendly ASDK features. As a result, the ASDK socialization successfully improved the efficiency and accuracy of health data recording, supporting the creation of more integrated and responsive primary healthcare services in Tulungagung Regency.